2005
DOI: 10.1021/ja042388u
|View full text |Cite
|
Sign up to set email alerts
|

Fluorination and Electrical Conductivity of BN Nanotubes

Abstract: Fluorination of BN nanotubes has been performed using a catalytic growth method, which leads to the appearance of markedly curved fluorine-doped BN sheets and converts originally insulating BN nanotubes to semiconductors, as confirmed by the comparative electron transport four-probe measurements on doped and undoped individual BN nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
169
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(181 citation statements)
references
References 16 publications
7
169
0
1
Order By: Relevance
“…One may concern the stability of the adsorption of F atoms on BNNTs since experimental studies indicated that the doped fluorine escapes easily when the tube is exposed to air or under standard beam irradiation in the electron microscope. [5] Our results indicate that the adsorption of F on BNNTs is as easy as the substitution of F for N in BNNTs in the B rich environment, and the formation of A B F is much easier than that of S N F in the N rich environment, as can be seen from their formation energies. Our nudged elastic band (NEB) [11] calculations indeed show that the F dissociation in single-walled BNNTs with adsorption of F atoms is easier than that in S [5] instead of doping F after the stage of BNNTs growth.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…One may concern the stability of the adsorption of F atoms on BNNTs since experimental studies indicated that the doped fluorine escapes easily when the tube is exposed to air or under standard beam irradiation in the electron microscope. [5] Our results indicate that the adsorption of F on BNNTs is as easy as the substitution of F for N in BNNTs in the B rich environment, and the formation of A B F is much easier than that of S N F in the N rich environment, as can be seen from their formation energies. Our nudged elastic band (NEB) [11] calculations indeed show that the F dissociation in single-walled BNNTs with adsorption of F atoms is easier than that in S [5] instead of doping F after the stage of BNNTs growth.…”
mentioning
confidence: 52%
“…[5] Our results indicate that the adsorption of F on BNNTs is as easy as the substitution of F for N in BNNTs in the B rich environment, and the formation of A B F is much easier than that of S N F in the N rich environment, as can be seen from their formation energies. Our nudged elastic band (NEB) [11] calculations indeed show that the F dissociation in single-walled BNNTs with adsorption of F atoms is easier than that in S [5] instead of doping F after the stage of BNNTs growth. We suppose that F adsorption occur in the stage of BNNTs growth, the F adsorbed on the inner walls of the multiwalled BNNTs should be stable.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…By combining this technique with scanning probe lithography, a pristine graphene nanoribbon has been isolated within a matrix of partially fluorinated graphene 44 . In addition, encouraging results have been already reported on the partial fluorination of BN nanotubes 45 and nanosheets 46 .…”
Section: Resultsmentioning
confidence: 90%
“…and might have superior unique mechanical, thermal, and electronic properties [45]. In addition, BN nanotubes are characterized by chemical inertness and poor wetting [46].…”
Section: Introductionmentioning
confidence: 99%